EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TGT BERBANTUAN APLIKASI KAHOOT UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK MATERI TEKANAN ZAT KELAS VIII SMP (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe the effectiveness of the TGT type cooperative learning model (Team Games Tournament) assisted by the kahoot application in improving cognitive learning outcomes, and to determine the differences in cognitive learning outcomes of students who apply the TGT type cooperative learning model assisted by the kahoot application with the conventional model class VIII MTs N. 1 Meranti Islands. The type of research used is quasi-experimental using Posttest Only Nonequvalent Control Group Design. The population of this study were 192 students of class VIII MTs N 1 Meranti Islands. The samples of this study were students of class VIII A as the control class and class VIII B as the experimental class. The data collection instrument was in the form of a cognitive learning outcome test for class VIII students on substance pressure. Data analysis was carried out by descriptive analysis and inferential analysis using the SPSS version 23 application. The results of this study indicate that there are differences in student cognitive learning outcomes between the control and experimental groups and the use of the TGT type cooperative learning model assisted by the Kahoot application is effectively used to improve student cognitive learning outcomes. class VIII MTs N 1 Meranti Islands on the subject of Substance Pressure.Key Words : Cooperative Learning Model TGT type, Cognitive Learning Outcomes,Substance Pressure